Quality Control To Reduce Defect In Packaging Using Six Sigma And FMEA Methods At PT XYZ: Pengendalian Kualitas Untuk Mengurangi Defect pada Kemasan Menggunakan Metode Six sigma Dan FMEA Pada PT XYZ - Ammalya A. Fertansyah; Mega CPA. Islami (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2025)
PT XYZ is one of the largest food and beverage companies in Indonesia. In carrying out the production process, the company always strives to produce good products with minimal defects. Defects in the production process are unavoidable. Therefore, a study needs to be conducted to determine the factors that cause packaging defects. The methods used in this study are Six sigma and failure mode effect analysis (FMEA). Based on the results of the study, the three highest types of defects for biscuits were obtained, namely cutter seal cookies, folded packaging, and scratched packaging. The average sigma value was 3.59 with a possible defect of 18329.7 for one million processes. Furthermore, based on the analysis using the FMEA method, the main priority of improvement based on the highest Risk Priority Number (RPN) value that must be carried out by PT XYZ is directed at the cause of the cutter seal (KKC) clamp cake defect with a non-standard dimension with an RPN value of 240, the cause of the packaging defect folding the slide rail plate with an RPN value of 180, and the cause of the KKC cake defect setting the non-standard disc feeding with an RPN value of 144. It is hoped that this study will be able to reduce product packaging defects so as to generate maximum profits.